The Battle of Sudbishchi in June 1555 in the appraisals of Russian chroniclers and historians of the 16th–17th centuries - Belov N.V. (Золотоордынское обозрение, 2022)
Research objectives: An analysis of Russian narrative sources in the 16th–17th centuries about the Battle of Sudbishchi; the identification and explanation of different assessments of the results of the battle in chronicles, publications, and other historical works of the Moscow State in the era. Research materials: Official, regional, and private chronicles of the 16th–17th centuries, publications (works of Ivan the Terrible and Andrei Kurbsky), and later historical compilations of the Old Russian tradition. Results and novelty of the research: In the Russian narrative sources of the 16th–17th centuries, the results of the battle between the Crimean Khan Devlet Giray I and the Tsar’s voivode, Ivan Bolshoy Sheremetev, at Sudbishchi received different appraisals. In the second half of the 16th century, the official governmental discourse considered this event to be an total, though costly, victory of Russian arms. The unofficial compositions of this period, in contrast, contained information about significant human losses and in general about the defeat of the Russian army. This was due not so much to the activity of state propaganda as to the inability of regional scribes to assess the global strategic consequences of the battle that were known to court chroniclers. Predominantly, the compilative character of the 17th century chronicles contributed to the affirmation of the governmental view of the battle among the Russian scribes. The first Russian historians of 18th–19th centuries accepted it, and through their mediation, a number of our contemporary researchers likewise shared their view. The Appendix of the article contains publications of three previously unknown accounts about the Battle of Sudbishchi from unpublished chronicles.